International mobility of angolan masters and PHD students: a literature review - Ladislau, Emílio (2021)
The results of “globalization”, understood here in its contemporary form, inseparable from the changes created in the last decades of the XX century, are far from being unanimously seen as merely positive. It is acknowledged, for example, that inequality and the centralization of wealth in the world tend to intensify, and it is in this perspective that we affirm that peripheral countries tend to lose out to central countries (Oliveira & Sangreman, 2015). Although improvements in living conditions are verifiable in many developing countries, as Angola, for example, they remain as development aid receivers and donors of resources to more developed countries (Oliveira & Sangreman 2015). Among these resources, we highlight human capital, namely master and PhD candidates that are pushed to migrate not only to obtain higher education training in more consolidated systems and higher education institutions, but also to pursue better living conditions in the recipient countries. More specifically, the study focuses on Angolan master and PhD candidates that left Angola to continue and conclude higher education training in Portuguese higher education institutions. Through a systematic review of the literature, this study addresses two main objectives: i) to understand how the literature looks at the topic of international mobility. More specifically, it is intended to identify the study perspectives of research already developed, whether they address public policies or whether they simply relate the issue of international mobility and / or brain drain without referring to any type of public policy. Simultaneously, it is intended to understand how this phenomenon – migration/mobility periods abroad affect master's and doctoral students (and already Doctorates) and to identify what is being done to tackle this issue. Scopus and Web of Science (WoS) databases were used to search our corpus of literature. A preliminary analysis of the studied literature allows us to conclude that, up to present, studies carried out on the theme of international mobility and / or brain drain targeting Angola is still insignificant. However, it is relevant to mention that in the West, and in other parts of the world, this theme has captured a lot of interest in the academic field, particularly in higher education studies. The existing literature has been concerned with addressing the topic from the perspective of the motivations and possible gains / losses of the countries of origin and host of these mobilities and migrations. Still, the topic of international mobility and brain drain dismiss developing countries as object of study. We believe that public policies (or their absence) play a fundamental role in motivating qualified people to migrate and return to their home countries, and therefore more research is needed to analyze existing policies and best practices in this domain. This reflection aims thus to shed light on the need for governments, especially from developing countries, such as Angola, to invest more in higher education policies framed into the national context and needs.